2022
DOI: 10.3310/xcuw1239
|View full text |Cite
|
Sign up to set email alerts
|

How public health teams navigate their different roles in alcohol premises licensing: ExILEnS multistakeholder interview findings

Abstract: Background In England and Scotland, local governments regulate the sale of alcohol by awarding licences to premises to permit the sale of alcohol for consumption on or off the premises, under certain conditions; without such a licence, alcohol cannot be legally sold. In recent years, many local public health teams have become proactive in engaging with alcohol licensing, encouraging licensing authorities to act in ways intended to improve population health. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…57 Qualitative data from the same study suggested that public health input was largely valued and was slowly reorienting the licensing system in some areas, especially in Scotland. 58,59 It is likely that any public health impact is limited in its effects by limitations in the licensing system more generally, which cannot reduce availability or effectively address remote alcohol sales, though large-scale studies have found some effects. 60,61 Either way, by engaging in licensing, PHTs can gather intelligence to better understand and communicate the limitations that exist from a public health perspective.…”
Section: Discussionmentioning
confidence: 99%
“…57 Qualitative data from the same study suggested that public health input was largely valued and was slowly reorienting the licensing system in some areas, especially in Scotland. 58,59 It is likely that any public health impact is limited in its effects by limitations in the licensing system more generally, which cannot reduce availability or effectively address remote alcohol sales, though large-scale studies have found some effects. 60,61 Either way, by engaging in licensing, PHTs can gather intelligence to better understand and communicate the limitations that exist from a public health perspective.…”
Section: Discussionmentioning
confidence: 99%
“…PHTs and other stakeholders in licensing must articulate evidence-based arguments when making licensing policies and decisions (O’Donnell et al., 2022 ). Our findings should help them to be clearer about their rationale, and help them to consider how/why specific policies or decisions will have impact.…”
Section: Discussionmentioning
confidence: 99%
“…Separate topic guides were developed for each of the five stakeholder groups, as this was part of a larger study which also explored interviewee roles, responsibilities and purpose in the licensing system (findings have been published separately, alongside a detailed description of the role and remit of key stakeholder groups in the licensing system, for which there are differences in Scotland and England (Fitzgerald et al., 2023 b; O’Donnell et al., 2022 )) Each topic guide was based on alcohol licensing literature and team discussion, including open-ended questions ( Supplementary Table 1 ) to elicit views on the ways in which temporal and spatial availability interventions impact on a range of alcohol-related harms. In total, 29 interviewees were based in England and 24 were based in Scotland.…”
Section: Methodsmentioning
confidence: 99%
“…Separate topic guides were developed for the five stakeholder groups [public health, licensing managers/officers, elected members, police (licensing) officers and licensing lawyers/clerks] based on existing alcohol licensing literature and research team discussion. The topic guides (summarised in O'Donnell et al 5 ) included a focus on interviewee roles, responsibilities and purpose in the licensing system, public health approaches to engaging in licensing, and interviewee views on such approaches and the ways in which temporal and spatial availability impact on alcohol harms. Interviews lasted between 32 and 156 minutes (median = 72 minutes) and were audio-recorded.…”
Section: Recruitment Sampling Data Collection and Analysismentioning
confidence: 99%